Molecular Underpinnings of Fe(III) Oxide Reduction by Shewanella Oneidensis MR-1 - Shi, Liang; Rosso, Kevin M.; Clarke, Thomas A.; Richardson, David J.; Zachara, John M.; Fredrickson, James K. (Frontiers in Microbiology, 2012)
In the absence of O2 and other electron acceptors, the Gram-negative bacterium Shewanella oneidensis MR-1 can use ferric [Fe(III)] (oxy)(hydr)oxide minerals as the terminal electron acceptors for anaerobic respiration. At circumneutral pH and in the absence of strong complexing ligands, Fe(III) oxides are relatively insoluble and thus are external to the bacterial cells. S. oneidensis MR-1 and related strains of metal-reducing Shewanella have evolved machinery (i.e., metal-reducing or Mtr pathway) for transferring electrons from the inner-membrane, through the periplasm and across the outer-membrane to the surface of extracellular Fe(III) oxides. The protein components identified to date for the Mtr pathway include CymA, MtrA, MtrB, MtrC, and OmcA. CymA is an inner-membrane tetraheme c-type cytochrome (c-Cyt) that belongs to the NapC/NrfH family of quinol dehydrogenases. It is proposed that CymA oxidizes the quinol in the inner-membrane and transfers the released electrons to MtrA either directly or indirectly through other periplasmic proteins. A decaheme c-Cyt, MtrA is thought to be embedded in the trans outer-membrane and porin-like protein MtrB. Together, MtrAB deliver the electrons through the outer-membrane to the MtrC and OmcA on the outmost bacterial surface. MtrC and OmcA are the outer-membrane decaheme c-Cyts that are translocated across the outer-membrane by the bacterial type II secretion system. Functioning as terminal reductases, MtrC and OmcA can bind the surface of Fe(III) oxides and transfer electrons directly to these minerals via their solvent-exposed hemes. To increase their reaction rates, MtrC and OmcA can use the flavins secreted by S. oneidensis MR-1 cells as diffusible co-factors for reduction of Fe(III) oxides. Because of their extracellular location and broad redox potentials, MtrC and OmcA can also serve as the terminal reductases for soluble forms of Fe(III). In addition to Fe(III) oxides, Mtr pathway is also involved in reduction of manganese oxides and other metals. Although our understanding of the Mtr pathway is still far from complete, it is the best characterized microbial pathway used for extracellular electron exchange. Characterizations of the Mtr pathway have made significant contributions to the molecular understanding of microbial reduction of Fe(III) oxides.